2015
DOI: 10.3390/molecules20034410
|View full text |Cite
|
Sign up to set email alerts
|

Phaleria macrocarpa Boerl. (Thymelaeaceae) Leaves Increase SR-BI Expression and Reduce Cholesterol Levels in Rats Fed a High Cholesterol Diet

Abstract: Abstract:In vitro and in vivo studies of the activity of Phaleria macrocarpa Boerl (Thymelaeaceae) leaves against the therapeutic target for hypercholesterolemia were done using the HDL receptor (SR-BI) and hypercholesterolemia-induced Sprague Dawley rats. The in vitro study showed that the active fraction (CF6) obtained from the ethyl acetate extract (EMD) and its component 2',6',4-trihydroxy-4'-methoxybenzophenone increased the SR-BI expression by 95% and 60%, respectively. The in vivo study has proven the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 37 publications
0
28
0
1
Order By: Relevance
“…to improve HDL levels and its related gene. 21 Other study also showed improved cholesterol profile, 29 thus supporting the potential effect of P. macrocarpa (Scheff.) Boerl as anti-atherosclerosis.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…to improve HDL levels and its related gene. 21 Other study also showed improved cholesterol profile, 29 thus supporting the potential effect of P. macrocarpa (Scheff.) Boerl as anti-atherosclerosis.…”
Section: Introductionmentioning
confidence: 83%
“…[17][18][19] Studies have proven its effect in the management of chronic diseases, such as hyperglycemia, dyslipidemia and kidney disorders. [20][21][22][23] Earlier studies have reported that P. macrocarpa (Scheff.) Boerl.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…And after 24 hours almost majority of NK cells are IFN-γ positive. IFN-γ is a potent activator of monocytes that allow macrophages to kill tumor cells and ingest microbes [35]. Another suggested mechanism is by flavonoid binding to the TNF family receptor triggering the IκB kinases complex to phosphorylate IκB.…”
Section: Mechanism Of Actions Of Phaleria Macrocarpa Extractmentioning
confidence: 99%
“…Another suggested mechanism is by flavonoid binding to the TNF family receptor triggering the IκB kinases complex to phosphorylate IκB. The NF-κB proteins translocate to the nucleus and bind the DNA binding sites inducing transcription of gene for the IFN-γ, TH1 immune response is activated and cellular mediated immunity orchestrated [35].…”
Section: Mechanism Of Actions Of Phaleria Macrocarpa Extractmentioning
confidence: 99%